ANALYSIS OF THE VALUES OF RELIGIOUS MODERATION IN ISLAMIC RELIGIOUS EDUCATION BOOKS CLASS IX 2013 CURRICULUM - Made Saihu; Abd Aziz (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
The aims of this study were (1) to describe the contents of the Islamic Religious Education and Moral Education book for class IX junior high school curriculum 2013. (2) To find out what the contents of the values of religious moderation are in the book Islamic Religious Education and Characteristics for Middle School Class IX curriculum 2013. This study uses library research methods (library research). The data sources consist of primary data and secondary data, the primary data is in the form of Islamic Religious Education books for Class IX Curriculum 2013 while the secondary data is in the form of journals, relevant research, books and articles. The analytical method used is the method of content analysis or content analysis. The results of research on the Islamic Religious Education Class IX Curriculum 2013 book show that it contains religious moderation values, namely the value of justice, the value of tolerance, the value of balance, and the value of building peace